2003
DOI: 10.1016/s1526-9523(03)00308-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation Strategies for Midwifery Education Linked to Digital Media and Distance Delivery Technology

Abstract: The goal of the teaching and learning process for health professionals is the acquisition of a fundamental core of knowledge, the demonstration of critical thinking ability, and the demonstration of competency in the performance of clinical skills. Teaching and learning in distance education programs require that the administration, teachers, and students be creative in developing evaluation strategies that can be adapted to the challenges of the cyberspace on-line educational environment. Evaluation standards… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
0
5
0
1
Order By: Relevance
“…Estudo de Caso Jones, Sheridan (17) Oermann, Truesdell, Ziolkowski (18) Wade (19) Staib 6Fullerton, Ingle (20) Zahner (21) Perciful, Nester (22) Adams, Gilman (23) Moule, Gilbert, Chalk (24) Posey, Pintz (25) Mahoney, Marfurt, Cunha (26)…”
Section: Continuaçãomentioning
confidence: 99%
See 1 more Smart Citation
“…Estudo de Caso Jones, Sheridan (17) Oermann, Truesdell, Ziolkowski (18) Wade (19) Staib 6Fullerton, Ingle (20) Zahner (21) Perciful, Nester (22) Adams, Gilman (23) Moule, Gilbert, Chalk (24) Posey, Pintz (25) Mahoney, Marfurt, Cunha (26)…”
Section: Continuaçãomentioning
confidence: 99%
“…Os estudantes podem utilizar a instrução assistida por computador para simular situações-problema em cenários clínicos (6) . Além disso, o uso da informática (20) facilita a Crossetti MGO, Bittencourt GKGD, Schaurich D, Tanccini T, Antunes M. Estratégias de ensino das habilidades do pensamento crítico na enfermagem. Rev Gaúcha Enferm., Porto Alegre (RS) 2009 dez;30(4):732-41.…”
Section: Aprendizagem Baseada Em Problemasunclassified
“…1 The drawbacks of this method include a high demand on resources, and limited reach due to geographical factors and restricted class sizes. [2][3][4] Also, mandated distance learning currently limits the number of dental students in the preclinical setting.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the online nature of the coursework of many midwifery programs, there is little published about innovative technologies used in midwifery education. Most of the literature related to online midwifery education was published 11 to 15 years ago, with the majority discussing issues such as changing courses to an online format, defining terms used in online education, and evaluating educational outcomes in online education . Now that online programs are proliferating, research that focuses on increasing the rigor of online education using innovative technology can take place.…”
Section: Introductionmentioning
confidence: 99%
“…Four of the studies revealed a positive effect for skill performance, whereas one study showed a negative effect . Thus, it is important that the translation of on‐campus courses to online delivery of coursework be student‐focused and enhance learning . In a recent qualitative analysis, 30 undergraduate and graduate nursing students from online programs agreed that productive online learning is achievable given adequate time‐management skills, sense of peer engagement and participation, and proficiency and confidence in writing .…”
Section: Introductionmentioning
confidence: 99%